INTEGRATING HINDU-BUDDIST HERITAGE OF BLITAR IN DIFFERENTIATED HISTORICAL LEARNING TO IMPROVE HISTORICAL COMPREHENSION - Wafiyatu Maslahah; Nur Al Maida (Media Bina Ilmiah, 2024)
The research was based on the problem of historical comprehension among students of private Islamic High School in Blitar. This study aims at 1) understanding the integration of Hindu-Buddhist heritage in Blitar Regency in differentiated historical learning to improve historical comprehension, 2) understanding the improvement of historical comprehension in differentiated historical learning by integrating the topic of Hindu-Buddhist heritage in Blitar Regency. Classroom action research was applied in this research. The sample of this research was the students of Madrasah Aliyah Assalam Jambewangi Selopuro Blitar and Madrasah Aliyah Al Muhtaduun Tlogo Kanigoro Blitar. The result showed that 1) the integration of Hidu-Buddhist heritage of Blitar Regency in differentiated historical learning helped the student in understanding historical events, 2) differentiated historical learning improved students’ historical comprehension by integrating the topic of Hindu-Buddhist heritage in Blitar. The average score of students’ pre-test was 68,45, and it increased to 81,4 in Cycle I and to 95,425 in Cycle II